Identification of candidate MYB transcription factors that influence CslF6 expression in barley grain - Garcia-Gimenez, Guillermo; Schreiber, Miriam; Dimitroff, George; Little, Alan; Singh, Rohan; Fincher, Geoffrey B.; Burton, Rachel A.; Waugh, Robbie; Tucker, Matthew R.; Houston, Kelly (Frontiers in Plant Science, 2022)
(1,3;1,4)-β-Glucan is a non-cellulosic polysaccharide required for correct barley grain fill and plant development, with industrial relevance in the brewing and the functional food sector. Barley grains contain higher levels of (1,3;1,4)-β-glucan compared to other small grain cereals and this influences their end use, having undesirable effects on brewing and distilling and beneficial effects linked to human health. HvCslF6 is the main gene contributing to (1,3;1,4)-β-glucan biosynthesis in the grain. Here, the transcriptional regulation of HvCslF6 was investigated using an in-silico analysis of transcription factor binding sites (TFBS) in its putative promoter, and functional characterization in a barley protoplast transient expression system. Based on TFBS predictions, TF classes AP2/ERF, MYB and bHLH were over-represented within a 1,000 bp proximal HvCslF6 promoter region. Dual luciferase assays based on multiple HvCslF6 deletion constructs revealed the promoter fragment driving HvCslF6 expression. Highest HvCslF6 promoter activity was narrowed down to a 51 bp region located -331 bp to -382 bp upstream of the start codon. We combined this with TFBS predictions to identify two MYB TFs: HvMYB61 and HvMYB46/83 as putative activators of HvCslF6 expression. Gene network analyses assigned HvMYB61 to the same co-expression module as HvCslF6 and other primary cellulose synthases (HvCesA1, HvCesA2 and HvCesA6), whereas HvMYB46/83 was assigned to a different module. Based on RNA-seq expression during grain development, HvMYB61 was cloned and tested in the protoplast system. The transient over-expression of HvMYB61 in barley protoplasts suggested a positive regulatory effect on HvCslF6 expression.